Bis[N′-(2-oxo-1H-indol-3-ylidene)furan-2-carbohydrazidato-κ3O,N′,O′]manganese(II) N,N-dimethylformide monosolvate monohydrate - Siti Nadiah Abdul Halim; Hapipah Mohd Ali; Seik Weng Ng (Acta Crystallographica Section E, 2010)
In the title compound, [Mn(C13H8N3O3)2]·C3H7NO·H2O, the metal atom is O,N,O′-chelated by two deprotonated Schiff bases and exists in a distorted octahedral geometry. The N–H groups, the carbonyl group of the DMF molecule and the uncoordinated water molecule engage in N—H...O and O—H...O hydrogen-bonding interactions, generating a hydrogen-bonded ribbon that propagates along [110].